2000
DOI: 10.2214/ajr.174.6.1741737
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of First-Pass and Delayed Contrast-Enhancement Patterns of Dysfunctional Myocardium on MR Imaging

Abstract: Evidence of delayed hyperenhancement of dysfunctional myocardium may be used to predict lack of mechanical improvement or nonviability, whereas the lack of hyperenhancement can be correlated with improvement of regional contractility or viability after revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 17 publications
2
59
0
3
Order By: Relevance
“…Recent clinical studies 5,6,11 suggest that normally enhanced dysfunctional myocardium can improve contractility after MI, whereas hypoenhanced myocardium remains dysfunctional. This has been demonstrated in the present study in a quantitative manner and is in agreement with pathological findings, which indicate that normally enhanced myocardium is noninfarcted, 4 whereas hypoenhanced myocardium represents necrotic tissue with microvascular damage and obstruction.…”
Section: Ce Mri For Prediction Of Segmental Functional Recoverymentioning
confidence: 99%
“…Recent clinical studies 5,6,11 suggest that normally enhanced dysfunctional myocardium can improve contractility after MI, whereas hypoenhanced myocardium remains dysfunctional. This has been demonstrated in the present study in a quantitative manner and is in agreement with pathological findings, which indicate that normally enhanced myocardium is noninfarcted, 4 whereas hypoenhanced myocardium represents necrotic tissue with microvascular damage and obstruction.…”
Section: Ce Mri For Prediction Of Segmental Functional Recoverymentioning
confidence: 99%
“…The classification techniques in the literature have typically relied on either visual inspection of images [6], which precludes quantitation, or manual delineation of the non-viable region [7,10], which can be time prohibitive. Semi-automatic segmentation techniques, based on the signal intensity characteristics of viable myocardium, have been used extensively in previous studies [8].…”
Section: Related Workmentioning
confidence: 99%
“…Recent clinical studies 14,16,17 demonstrated that normoenhanced dysfunctional myocardium can spontaneously improve contractility after MI, whereas myocardium with early hypoenhancement remains dysfunctional. This is in agreement with pathological findings that indicated that normally enhanced myocardium is noninfarcted, 5 whereas hypoenhanced myocardium represents necrotic tissue afflicted by microvascular damage and obstruction.…”
Section: Ce Mri For Myocardial Viabilitymentioning
confidence: 99%